1999
DOI: 10.1088/0953-8984/11/4/007
|View full text |Cite
|
Sign up to set email alerts
|

Photonic band gaps of three-dimensional face-centred cubic lattices

Abstract: We show that the photonic analogue of the Korringa-Kohn-Rostocker method is a viable alternative to the plane-wave method to analyze the spectrum of electromagnetic waves in a three-dimensional periodic dielectric lattice. Firstly, in the case of an fcc lattice of homogeneous dielectric spheres, we reproduce the main features of the spectrum obtained by the plane wave method, namely that for a sufficiently high dielectric contrast a full gap opens in the spectrum between the eights and ninth bands if the diele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
113
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 45 publications
7
113
0
Order By: Relevance
“…We study optical transmission at normal incidence on thin photonic crystals. In accordance with previous calculations, 5 we demonstrate that photonic crystals of high-index core and low-index shell particles posses a larger relative L-stopgap width in comparison to crystals of low-index core and high-index shell 17 or homogeneous particles.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We study optical transmission at normal incidence on thin photonic crystals. In accordance with previous calculations, 5 we demonstrate that photonic crystals of high-index core and low-index shell particles posses a larger relative L-stopgap width in comparison to crystals of low-index core and high-index shell 17 or homogeneous particles.…”
supporting
confidence: 92%
“…3 Indeed, the full vector calculations on an fcc crystal of core-shell particles have shown that the relative L-stopgap width (g w ) can be increased by more than 50% compared to the case of homogeneous particles. 5 Zinc sulfide (ZnS), due to its high bulk refractive index (β-ZnS n 589 = 2.36) and lack of absorption in the visible and near IR region, 9 is a convenient material for photonic applications. Spherical ZnS particles can be made with a wide range of sizes (100 -1500 nm in radius) and high monodispersity.…”
mentioning
confidence: 99%
“…This assumption also holds in the continuation of this section. There are several methods to obtain the solutions k( ) ω [4][5][6][7][8][9] . From these solutions, the dispersion relationships can be derived.…”
Section: Bloch Solutions In An Infinite Crystalmentioning
confidence: 99%
“…The results can be explained by the Maxwell-Garnett type effective medium theory. If the frequency of EM wave is less than ω p , the effective dielectric ε eff can be written as [48] …”
Section: The Unusual Properties Of Surface-plasmon Modesmentioning
confidence: 99%